In-flight calibration of magnetometers and low-cost SINS for small land-survey satellite - Somov, Yevgeny I.; Hajiyev, Chingiz (IEEE, 2014)
Magnetometers are widely used for attitude determination of the low Earth orbit satellites. In order to estimate the satellite attitude accurately, bias of magnetometer must be estimated. In this study a linear Kalman filter based algorithm for estimation of magnetometer biases is proposed. We present computer technology for onboard signal processing and in-flight calibration of a low-cost strap-down inertial navigation system (SINS) for small land-survey satellite. For the system with small financial expenditures on practical implementation, the requirements are not severe on accuracy of the attitude determination. In this situation, we have applied the SINS correction based on signals of a Sun optoelectronic sensor and magnetometer.